Perspectives for the Use of CAR-T Cells for the Treatment of Multiple Myeloma - Jasiński, Marcin; Basak, Grzegorz W.; Jedrzejczak, Wiesław W. (Frontiers in Immunology, 2021)
During recent years considerable progress has been made in the treatment of multiple myeloma. However, despite the current improvements in the prognosis of this malignancy, it always ends with relapse, and therefore new therapy approaches for destroying resistant cancer cells are needed. Presently, there is great hope being placed in the use of immunotherapy against refractory/relapsed multiple myeloma which is unresponsive to any other currently known drugs. The most promising one is CAR-T cell therapy which has already shown tremendous success in treating other malignancies such as acute lymphoblastic leukemia (ALL), and could potentially be administered to multiple myeloma patients. CAR-T cells equipped with receptors against BCMA (B-cell maturation antigen), which is a surface antigen that is highly expressed on malignant cells, are now of great interest in this field with significant results in clinical trials. Furthermore, CAR-T cells with other receptors and combinations of different strategies are being intensively studied. However, even with CAR-T cell therapy, the majority of patients eventually relapse which is the greatest limitation of this therapy. Serious adverse events such as cytokine release syndrome or neurotoxicity should also be considered as possible side effects of CAR-T cell therapy. Here, we discuss the results of CAR-T cell therapy in the treatment of multiple myeloma, where we describe its main advantages and disadvantages. Additionally, we also describe the current results that have been obtained on using combinations of CAR-T cell therapies with other drugs for the treatment of multiple myeloma.